Longitudinal study of carotid artery bifurcation geometry using magnetic resonance angiography. (June 2019) - NGO, Minh Tri; Kwak, Hyo Sung; Ho Chung, Gyung; Koh, Eun Jeong
Objectives: Geometry of carotid artery has been known as a risk factor for atherosclerotic carotid disease. Though aging and disease progression can both attribute to geometric changes in the arteries, the exact nature of this phenomenon remains elusive. The aim of our study was to investigate carotid artery geometric changes in a longitudinal study. Methods: We conducted a retrospective study of 114 subjects who underwent carotid contrast-enhanced magnetic resonance angiography at our clinic at baseline (2005 to 2007) and after 10 years. The right carotid arteries were segmented using semi-automated methods to obtain various measurements of carotid artery geometry. For each patient, these parameters were assessed at both time points, including bifurcation angle, internal carotid artery angle, vessel diameter, and circumference. Results: The median age for the total patient population ( n  = 114) at baseline was 59.06 ± 10.40 years. Mean time interval between baseline magnetic resonance angiography and magnetic resonance angiography after 10 years of these patients was 129.18 ± 7.77 months. For the whole group, there was a significant increase in the bifurcation angle ( p  < 0.05) over a 10-year period. A significant increase was also noted in the diameter and circumference of the common carotid artery ( p  < 0.05). However, the other vessel diameters and circumferences (bulb carotid, internal carotid) as well as the internal carotid angle did not significantly change ( p ≥ 0.05). Conclusions: The diameter and circumference of the common carotid artery and bifurcation angle significantly increased over a decade of life.